Examining the Mediating Role of Artificial Intelligence in Green Organizations, and Employee Sustainabilitty - Nurmala Pratiwi; Agus Arijanto (ARE Publisher, 2026)
Sustainability issues and the implementation of Environmental, Social, and Governance (ESG) principles have become a major concern in the modern banking sector in order to ensure stable long-term performance. Amidst industry competition and the digitalisation of financial services, banks are required to not only pursue profitability, but also maintain a balance between employee welfare and environmental sustainability. In the context of sustainable performance, green organisational culture, green transformational leadership, and perceived organisational support are important factors that influence sustainable employee performance, with artificial intelligence adaptation acting as a mediating variable. Objectives: This study aims to analyse the influence of green organisational culture, green transformational leadership, and perceived organisational support on sustainable employee performance at PT Bank BRI Pluit Branch, with artificial intelligence adaptation as a mediating variable in the perspective of sustainable business. Methodology: A quantitative survey was conducted using non probability purposive sampling, involving 119 respondents. The data were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) Finding: The results of the study indicate that green organisational culture, green transformational leadership, and perceived organisational support have a positive and significant effect on sustainable employee performance. The mediation test results show that artificial intelligence adaptation is unable to mediate the influence between leadership and organisational support on sustainable performance. Conclusion : AI technology has been adopted, but its effectiveness in improving performance still depends heavily on the readiness of human resources and the integration of work culture. Based on the results of this study, it is recommended that the management of PT Bank BRI Pluit Branch improve digital literacy and align workloads with organisational support in order to maintain consistent employee performance.